Community-based urban development : evolving urban paradigms in Singapore and Seoul - Cho, Im Sik; Križnik, Blaž, 1972- (Springer, 2017)
The book compares different approaches to urban development in Singapore and Seoul over the past decades, by focusing on community participation in the transformation of neighbourhoods and its impact on the built environment and communal life. Singapore and Seoul are known for their rapid economic growth and urbanisation under a strong control of developmental state in the past. However, these cities are at a critical crossroads of societal transformation, where participatory and community-based urban development is gaining importance. This new approach can be seen as a result of a changing relationship between the state and civil society, where an emerging partnership between both aims to overcome the limitations of earlier urban development. The book draws attention to the possibilities and challenges that these cities face while moving towards a more inclusive and socially sustainable post-developmental urbanisation. By applying a comparative perspective to understand the evolving urban paradigms in Singapore and Seoul, this unique and timely book offers insights for scholars, professionals and students interested in contemporary Asian urbanisation and its future trajectories.
Keywords: Urbanization -- Singapore.; Urbanization -- Korea (South) -- Seoul.; City planning -- Singapore.; City planning -- Korea (South) -- Seoul.; Korea (South) -- Seoul.; Singapore.; elektronické knihy; electronic books